Author Response: Clinical Outcome After Endovascular Treatment in Patients With Active Cancer and Ischemic Stroke: A MR CLEAN Registry Substudy. (26th July 2022) - Verschoof, Merelijne A.; Groot, Adrien E.; de Bruijn, Sebastiaan F.T.M.; Roozenbeek, Bob; van der Worp, H. Bart; Dippel, Diederik W.J.; Emmer, Bart J.; Roosendaal, Stefan D.; Majoie, Charles B.L.M.; Roos, Yvo B.W.M.; Coutinho, Jonathan M.
Abstract : We thank Moores and Ganesh for their comments on our research 1 and for drawing our attention to their 2 studies. 2, 3 Both these studies report on 4 patients with cancer, but do not state whether the cancer was active. It is difficult to obtain conclusive evidence from observational studies. We actually need an estimate of the interaction of cancer with treatment effect in a controlled trial. We also agree that when uncertainties remain, shared decision-making is essential. Hopefully, our studies will provide some needed insight into the treatment responses and outcomes of this challenging group of patients with active cancer.